Self-medication practices among public in Selangor: attitudes and patterns / Suhana Jawahir - Jawahir, Suhana (2015)
Irrational use of medications during self-medication may lead to senous consequences. Recently, there is a great concern about the self-medication practices among the Malaysian population. The study was aimed to explore the attitudes and patterns of self-medication practices among public aged 18 years old and above in Selangor. A validated questionnaire was administered to the public via both, webbased and paper-based self-administrated survey. 401 responses received, with 33.9% participants mentioned that they had practiced self-medication in the previous two weeks. The prevalence was generally higher among the middle age groups of 25 - 34 and 3 5 - 4 4 years, and participants aged 3 5 - 4 4 was associated with higher odds of self-medication practices compared to younger ones ( 1 8 - 2 4 years old) (p = 0.016). More than half (66.6%) of the participants had a satisfactory level of attitude towards self-medication practices. Gender (p < 0.034), marital status (p < 0.008) and whether the participant's occupation or participant's family's occupation related to healthcare (p < 0.046) were significantly associated with the level of attitude towards selfmedication practices. Two major reasons for practicing self-medication were the illness is a minor and previous experience or knowledge about the illness and treatment. Majority of the participants (83.8%) would look for information about medications before practicing self-medication and 58.4% of participants mentioned modern healthcare professionals as their source of information for self-medication. Although analgesics and cough or flu medicines were the most commonly used medications, herbs or traditional medicines were also used by the public when practicing self-medication. More than half (71.3%) of the participants mentioned pharmacy outlet as their main source of medications for practicing self-medication. This study also revealed the events of side effects experienced by the participants after practicing self-medication. Public need to be well-equipped with information regarding self-medication practices to ensure rational use of medications during selfmedication.